Clinical outcome of patients with differentiated thyroid cancer and raised antithyroglobulin antibody levels: a retrospective study - Manish Ora; Aftab Hasan Nazar; Prabhakar Mishra; Sukanta Barai; Amitabh Arya; Prasanta Kumar Pradhan; Sanjay Gambhir (Thyroid Research, 2021)
Abstract Background Thyroglobulin (Tg) is a specific tumor marker for differentiated thyroid cancer (DTC). However, in the presence of an antithyroglobulin antibody (TgAb), it becomes unreliable. The purpose of the study was to assess the long-term outcome of DTC patients with raised TgAb. Method In a retrospective study, we included patients with DTC who had raised TgAb following total thyroidectomy. We excluded patients with persistently raised Tg (≥ 1 ng/ml) or radioiodine avid disease. Serial TgAb levels, excellent response (ER), incomplete response (IR), and anatomical recurrence were evaluated. Results A total of seventy-six patients were included in the study. Patients with IR had higher baseline TgAb (1071.27 ± 1216.17 vs. 99.61 ± 91.29 IU/ml, p < 0.001) and central compartment lymph node metastases (70.8% vs. 46.4%, p = 0.035) in comparison to those in the ER group. In the first follow-up, 64 (84.2%) patients had a stable or fall in the TgAb (0 to − 98.3%). Sixty-eight patients received high-dose radioiodine therapy (RIT). Out of these, 59 (86.5%) had transient, and 51 (75%) had a long-term fall in TgAb. After a follow-up period of 58.74 ± 26.26 months, 63.2% (48 out of 76) patients had IR. Nine (11.8%) patients had a rising TgAb level (3.7–170.9%) from baseline. Eleven patients underwent 18F-FDG PET/CT, and five of them demonstrated metabolically active recurrent disease. Three patients underwent cervical lymph nodes dissection. None of the patients died during the follow-up period. Conclusion High post-operative TgAb levels and central compartment lymph nodal metastases are risk factors for IR. RIT leads to a significant fall in the TgAb in these patients. The low level of raised TgAb is associated with an excellent outcome. Patients with recurrences had very high baseline TgAb > 1000 IU/ml. Raised TgAb was associated with good clinical outcomes and not associated with increased mortality.